Too Much to Digest: How Transparency and Social Buzz Fuel Gluten-Free Confusion - Tjokro, Hadi Wijaya; Teofilus, Teofilus; Kaihatu, Thomas Stefanus; Efrata, Tommy Christian; Rizqi, Osama (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to analyze the relationship between information transparency, information ambiguity, and information overload on gluten-free products, as well as the influence of social contagion on the relationship. The research method used is a survey by distributing questionnaires to consumers of gluten-free products. The results of the study indicate that there is a significant positive correlation between information transparency and information ambiguity, and a positive correlation between information ambiguity and information overload. In addition, social contagion has also been shown to moderate the relationship between these variables. These findings indicate that consumers want clear, complete, and relevant information about gluten-free products. However, they are often faced with ambiguous and excessive information, which can cause confusion and difficulty in making decisions. Social media plays an important role in disseminating information about gluten-free products, both accurate and inaccurate. This study suggests the importance of increasing information transparency, reducing ambiguity, and managing the dissemination of information through social media to increase consumer satisfaction with gluten-free products.